Peran Sio (Perantara) dalam Arena Pernikahan Adat di Desa Ononazara Kecamatan Tugala Oyo Kabupaten Nias Utara - Agusman Zebua; Masniar Sitorus; Roida Lumbantobing; Martua Sihloho; Wensdy Sitindaon (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the role of Sio as an intermediary in traditional Nias marriage ceremonies in Ononazara Village, Tugala Oyo District, North Nias Regency. The focus is directed toward how the Sio positions himself within the customary social arena and how social, cultural, and symbolic capital serve as the foundation of his legitimacy and authority. The research problem arises from the phenomenon of social change, where the authority of parents and traditional leaders, once dominant, is now shared with the presence of the Sio as a central mediator. The study employs a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation, validated by triangulation of sources, methods, and theories. Data analysis uses Pierre Bourdieu’s concepts of social capital and social arena to reveal the dynamics of power relations in customary practices. The findings indicate that the Sio is not merely a spokesperson but a key actor who maintains harmony, mediates Böwö (bridewealth) negotiations, and ensures effective communication between families. His position is shaped by kinship networks, deep knowledge of customs and ritual language, and social reputation. In the context of modernization, the Sio functions as both a cultural conservator and adaptive mediator who balances economic and symbolic dimensions in traditional Nias marriages.